1969
DOI: 10.1039/j29690000439
|View full text |Cite
|
Sign up to set email alerts
|

Substituent effects in the mass spectra of some γ- and β-substituted methyl butyrates

Abstract: Results are presented (relative ion abundances, I.P. and A.P. measurements) to illustrate substituent effects in the mass spectra of some y-and P-substituted methyl butyrates. It is argued that (i) ' sub-decomposition energy ' ions and (ii) competition in the source with fast fragmentation processes are important factors influencing parent/ daughter ion ratios, which are then rationalised in terms of the variation of these two factors with substituent. In certain cases a substituent effect on the energy of act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

1971
1971
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…The m/z = 74 fragment ion is the dominant contributor to the total photoionization above 10.4 eV, augmented by the m/z = 71 C 4 H 7 O + and m/z = 87 C 4 H 7 O 2 + fragment ions with respective appearance energies of 10.9 ± 0.1 and 10.85 ± 0.1 eV. Howe et al [21] reported an appearance energy of 11.2 ± 0.2 eV for the m/z = 71 C 4 H 7 O + fragment ion, corresponding to direct loss of the CH 3 O radical. The CH 3 radical loss channel associated with formation of the m/z = 87 C 4 H 7 O 2 + fragment ion seen here has not been previously reported.…”
Section: Methyl Butanoatementioning
confidence: 98%
See 3 more Smart Citations
“…The m/z = 74 fragment ion is the dominant contributor to the total photoionization above 10.4 eV, augmented by the m/z = 71 C 4 H 7 O + and m/z = 87 C 4 H 7 O 2 + fragment ions with respective appearance energies of 10.9 ± 0.1 and 10.85 ± 0.1 eV. Howe et al [21] reported an appearance energy of 11.2 ± 0.2 eV for the m/z = 71 C 4 H 7 O + fragment ion, corresponding to direct loss of the CH 3 O radical. The CH 3 radical loss channel associated with formation of the m/z = 87 C 4 H 7 O 2 + fragment ion seen here has not been previously reported.…”
Section: Methyl Butanoatementioning
confidence: 98%
“…The m/z = 74 C 3 H 6 O 2 + and m/z = 71 C 4 H 7 O + fragment ions are prominent with respective appearance energies of 10.18 eV [52] and 11.2 ± 0.2 eV [21]. The structure of the m/z = 74 fragment ion was identified by Holmes and Lossing [52] to be the methyl acetate enol ion CH 2 COHOCH 3 + formed with the loss of C 2 H 4 by direct bond cleavage of the low-energy distonic CH 2 CH 2 CH 2 COHOCH 3 + ion, formed by prior isomerization of the methyl butanoate parent ion.…”
Section: Methyl Butanoatementioning
confidence: 99%
See 2 more Smart Citations
“…The production of esters as biofuel surrogates from vegetable oils and fatty acids through transesterification reactions has been studied extensively. , MB has also shown promise of being generated from nonfood crops, thus allowing it to qualify as a second-generation biofuel. The photoionization of MB has been studied by photoelectron spectroscopy and photoionization mass spectrometry. Mazyar et al have analyzed the ethene loss dissociative photoionization dynamics after parent ion isomerization by PEPICO and provided a 0 K appearance energy, E 0 = 10.275 ± 0.010 eV, to the enolic form of the methyl acetate cation at m / z 74, along with the associated microcanonical rate curve. In a more recent photoionization mass spectrometry (PIMS) study to determine absolute photoionization cross sections, Wang et al have also proposed appearance energies of 10.90 ± 0.10 and 10.85 ± 0.10 eV for the m / z 71 and 87 daughter ions, respectively, along with an appearance energy of 10.15 ± 0.10 eV for the dominant m / z 74 fragment ion …”
Section: Introductionmentioning
confidence: 99%